2002
DOI: 10.1161/hc0602.103396
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Production of Vascular Endothelial Growth Factor and fms -Like Tyrosine Kinase-1 Receptor in Acute Kawasaki Disease

Abstract: Background — Increased vascular permeability is an important event during the initial process of Kawasaki disease (KD). One potential responsible candidate for the induction of vascular hyperpermeability is vascular endothelial growth factor (VEGF). Methods and Results — We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 14 publications
1
78
0
Order By: Relevance
“…46 Vascular endothelial growth factor (VEGF), monocyte chemotactic and activating factor (MCAF or MCP-1), tumor necrosis actor-␣ (TNF-␣), and various interleukins also appear to play important roles in the vasculitic process. [47][48][49][50][51][52][53][54] …”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…46 Vascular endothelial growth factor (VEGF), monocyte chemotactic and activating factor (MCAF or MCP-1), tumor necrosis actor-␣ (TNF-␣), and various interleukins also appear to play important roles in the vasculitic process. [47][48][49][50][51][52][53][54] …”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…In fact, pathological studies have revealed that CAL in KD are characterized by subendothelial oedema, vascular EC damage and the infiltration of inflammatory cells [21,22]. On the other hand, an active remodeling process has been reported to occur in the CAL of acute KD [14,15] which thereafter continues several years after the onset of KD [16]. VEGF can recruit endothelial progenitor cells from the bone marrow into the peripheral circulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Yasukawa et al . [14] reported that CAL in acute KD had abundant expression of VEGF and its receptors. Matrix matalloproteinases (MMP)-2 and -9 were expressed at the CAL in KD, thus suggesting that angiogenesis occurs in the remodeling process of the arterial walls in acute KD vasculitis [15].…”
Section: Introductionmentioning
confidence: 99%
“…46 Vascular endothelial growth factor (VEGF), monocyte chemotactic and activating factor (MCAF or MCP-1), tumor necrosis factor-␣ (TNF-␣), and various interleukins also appear to play important roles in the vasculitic process. [47][48][49][50][51][52][53][54] …”
Section: Etiology and Pathogenesismentioning
confidence: 99%